Urban Accessibility / Mobility Index Feasibility Stage Report - World Bank (Washington, DC, 2014)
Given the increasing importance of the urban transport sector, the World Bank decided to explore the feasibility of setting up a possible urban accessibility/mobility index. The purpose of such an index would be to provide an indicator / measurement, of how urban transport systems in different cities compared to one another, and how the transport system developed in each individual city. The aim is to provide client cities and countries, along with the World Bank and other institutions, with some evidence-based information. It is for this reason that the Bank decided to develop a suitable index. However, urban transport has multiple dimensions, and cannot be comprehensively assessed by a single indicator. There is an acute lack of reliable data on different aspects concerning urban transport. Therefore, a compromise was decided upon, in order to develop an index that was both comprehensive and practical. The compromise required that data for the index / indicators should be easy to collect, easy to interpret and understand, and replicable from one city to another. It was also essential that the data be regularly updated and easily available. The core urban transport policy of the Bank is to help countries and cities develop policies that favor public transport and non-motorized transport modes, versus private cars and motorcycles. The outline design of the urban accessibility/mobility index explored in this feasibility stage report, has been envisaged to indeed reflect these objectives.